A retrospective analysis of post-mortem procedures of sudden unexpected death in the young investigated at Salt River Forensic Pathology Services, Cape Town - Hamadziripi, Dirk M (Department of Pathology, 2023)
Sudden unexpected death in the young (SUDY) is the demise of a seemingly healthy individual aged between one and 40 years. The scope of SUDY investigation varies and there is little research regarding SUDY at Salt River Mortuary (SRM). Accordingly, the objectives of this study were to determine the number of SUDY cases admitted to SRM, document the scope of investigations, and identify candidates for retrospective molecular autopsies. A total of 1088 cases were admitted between 1 January 2010 and 31 December 2015, representing 3.3% (1088/32812) of the entire case load, 30 were excluded as the files were missing. Full autopsies (56.7%; 600/1058) were preferred to partial autopsies (5.6%; 59/1058) and external autopsies (37.7%; 399/1058). The most utilised ancillary tests were LODOX imaging (86.6%, 916/1058) and toxicology (34.8%; 368/1058). Specificity of cause of death was seen to be significantly associated with the extent of autopsy. A total of 35.7% (378/1058) of the cases were established as candidates for molecular autopsy on the criteria of being undetermined, having unspecific causes of death or having specific causes of death that are deemed hereditary. Findings of this study show that SUDY cases do not always undergo all ancillary tests coupled with retention of biological samples. These findings provide insight into the current gaps in the investigation of SUDY cases at SRM and highlight areas for improvement.